RESPONSIBILITY OF THE BOARD OF DIRECTORS OF STATE-OWNED ENTERPRISES (BUMN) AS MANAGEMENT OF STATE PROPERTY AND AS PROFIT-BASED BUSINESS MANAGEMENT - IRMAN PUTRA; ARIEF FAHMI LUBIS (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Directors often face dilemmas in making business decisions in buying and or selling assets, shares, investment, expansion because they have two sides of supervision. If they are always restrained by fear and fear in making decisions, the business movement will definitely be hampered. The approach method used in this research is a sociological juridical approach using secondary data and reinforced by primary data. Secondary data was obtained from laws and regulations and interviews with informants, and questionnaires who had served as Directors in BUMN, while secondary data was obtained from the statute approach and conceptual approach. The data obtained from this study were then analyzed qualitatively to answer the problems in this study. The results of this study indicate that the decision of the Board of Directors in business if it is based on good faith cannot be blamed, either civilly or criminally. However, if the Board of Directors is guilty (schuld) and/or negligent (culpoos), the members of the Board of Directors are fully responsible personally and jointly and severally (Article 97 paragraph (3), (4) and (5) of the Company Law). The Board of Directors personally can also be bankrupt so that it is not only PT that is obliged to pay its obligations, the Board of Directors must also be responsible for paying debts.